2020
DOI: 10.1038/s41598-020-60633-y
|View full text |Cite
|
Sign up to set email alerts
|

Toward Low-Cost All-Organic and Biodegradable Li-Ion Batteries

Abstract: this work presents an alternative method for fabricating Li-ion electrodes in which the use of aluminum/copper current collectors and expensive binders is avoided. Low-cost natural cellulose fibers with a 2-mm length are employed as binder and support for the electrode. The objective of this method is to eliminate the use of heavy and inactive current collector foils as substrates and to replace conventional costly binders with cellulose fibers. Moreover, no harmful solvents, such as N-methylpyrrolidone, are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 78 publications
0
35
0
Order By: Relevance
“…Delaporte et al recently reported on a flexible Li-ion battery that utilizes cellulose fibers as binder and support for the electrode and active materials when mixed with different carbons or redox active materials (such as LiFePO 4 (LFP), Li 4 Ti 5 O 12 (LTO), or organic 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA)). [144] Their best battery achieved a capacity of 160 mAh g −1 (without encapsulation) with LTO electrodes and about 80 mAh g −1 with PTCDA electrodes.…”
Section: Batteriesmentioning
confidence: 99%
“…Delaporte et al recently reported on a flexible Li-ion battery that utilizes cellulose fibers as binder and support for the electrode and active materials when mixed with different carbons or redox active materials (such as LiFePO 4 (LFP), Li 4 Ti 5 O 12 (LTO), or organic 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA)). [144] Their best battery achieved a capacity of 160 mAh g −1 (without encapsulation) with LTO electrodes and about 80 mAh g −1 with PTCDA electrodes.…”
Section: Batteriesmentioning
confidence: 99%
“…In addition, PTCDA is a semiconducting material. 46,47 For these reasons, the coating of LTO particles with PTCLi 4 was of interest to yield a material with a good surface conduction of Li-ions and electrons. In addition, the thin PTCLi 4 layer can provide overcharge protection in a full-cell configuration, as its redox potential is lower than that of LTO.…”
Section: Ptcli 4 Coating On the Lto Surfacementioning
confidence: 99%
“…The modified carbon is first dispersed in deionized water to obtain a perfect and homogeneous suspension, as shown in Fig. 2 a,b, for CNT–COOH 38 . Further, an excess NMC (99 or 99.5 wt% of the total solid mass) is added to the solution and mixed thoroughly.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of water-soluble carbons: VGCF-COOH and CNT-COOH. The modification procedure was adapted from a recent work 38 . 5 g of carbon (VGCF or CNT, see Fig.…”
Section: Methodsmentioning
confidence: 99%